Concentração de metais em tecidos de girinos de rãs-touro, Aquarana catesbeiana (Shaw, 1802), expostos às águas do Rio Sorocaba - Arjonas, Victor Holanda (2024)
Environmental monitoring through bioindicators is an essential strategy for understanding the impacts that may occur on water bodies. Bullfrog tadpoles were used to verify the effect of exposure to metals present in river water, verifying the potential for biomonitoring of water bodies using this species. Water was collected at 2 points on the Sorocaba River, one in the city of Ibiúna, representing the source of the river (PI) and another in the Itupararanga Reservoir (PIR), during the dry season of the year. Rã-Touro tadpoles were exposed to the collected water for 96 hours and, at the end of the test, the animals were anesthetized and killed for the collection of samples of gills, skin and caudal muscle, where the concentration of metallothionein proteins (MTs) and the metals arsenic (As), barium (Ba), cadmium (Cd), lead (Pb), cobalt (Co), copper (Cu), strontium (Sr), manganese (Mn), molybdenum ( Mo), nickel (Ni) and zinc (Zn). The concentration of metallothionein, in the samples of gills and caudal muscle, showed a significant increase in the tadpoles exposed to the waters of the Itupararanga Reservoir, in relation to the control and the samples of the tadpoles exposed to the waters collected in Ibiúna (PI). The metals Ba, Cu, Mn, Sr, Zn were in higher concentration in the gill and skin samples of the group exposed to the waters of the Itupararanga Reservoir compared to the control. Gills showed a strong correlation between MTs and metals. The results show different effects on the tissues and potential evidence of the use of this biomarker using the gills, which constitute an interface between the aquatic environment and the internal environment of the animal, which proved to be an important organ for use in environmental biomonitoring.